A technique for fast and safe collection of urine in newborns (Journal of Kathmandu Medical College, 2017)
Background: Urine collection in children especially in new born is a great challenge. A wide range of clinical interventions for urine collection is described in the literature, including non-invasive and invasive methods. Mid-stream urine collection is considered the most appropriate technique for older children. Here we are testing a method for obtaining mid- stream urine sample in newborns.Objective: To test a technique of urine collection for obtaining mid-stream urine sample in newborns.Method: A prospective feasibility study of a technique of urine sample collection based on bladder and lumbar stimulation maneuvers done in 100 newborns of less than 28 days of life over a period of one month. The main variable was the success rate in obtaining a midstream urine sample collection within four minutes and secondary variables were time required to obtain the sample and associated complications.Results: Mid- stream urine sample was collected successfully in 91% of babies. Mean time required for urine collection was 59.7 seconds with standard deviation of 46.4 seconds and median time was 47 seconds. No untoward complication other than controlled crying was seen.Conclusion: This is a quick and safe technique for mid-stream urine sample collection in newborn with high success rate and minimal discomfort.Journal of Kathmandu Medical CollegeVol. 5, No. 3, Issue 17, Jul.-Sep., 2016, Page: 82-84